The Effect Of Islamic Corporate Governance, Islamic Corporate Social Responsibility, And Islamicity Performance Index On The Financial Performance Of Sharia Commercial Banks In Indonesia - Wahyuningtyas, Ida Puspitarini; Lutfiana, Dwi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The performance growth of Islamic commercial banks in Indonesia cannot be said to be good enough considering that Islamic commercial banks have been established for 30 years, therefore it is necessary to examine what factors can affect the performance of Islamic commercial banks. The purpose of this study is to determine the partial or simultaneous influence of Islamic Corporate Governance (ICG), Islamic Corporate Social Responsibility (ICSR) and Islamicity Performance Index (IPI) variables on the Financial Performance of Islamic Commercial Banks in Indonesia in 2016-2020. This study uses quantitative research methods. The population in this study were 14 Islamic commercial banks in Indonesia. The sample in this study were 5 Islamic commercial banks in Indonesia. The research method used is multiple linear regression analysis technique. The results show that the ICG and Zakat Performance Index (ZPI) variables have a significant effect on the financial performance of Islamic commercial banks in Indonesia in 2016-2020. While the ICSR and Profit Sharing Ratio (PSR) variables have no significant effect on the financial performance of Islamic commercial banks in Indonesia in 2016-2020. The variables ICG, ICSR, PSR, and ZPR simultaneously affect the financial performance of Islamic commercial banks in Indonesia in 2016-2020.